Short-term effects of high-resolution (1-km) ambient PM2.5 and PM10 on hospital admission for pulmonary tuberculosis: a case-crossover study in Hainan, China - Zhu, Pan-Pan; Gao, Yi; Zhou, Gui-Zhong; Liu, Rui; Li, Xiao-Bo; Fu, Xian-Xian; Fu, Jian; Lin, Feng; Zhou, Yuan-Ping; Li, Li (Frontiers in Public Health, 2023)
There is limited evidence regarding particulate matter (PM) 's short-term effects on pulmonary tuberculosis (PTB) hospital admission. Our study aimed to determine the short-term associations of the exposure to ambient PM with aerodynamic diameters <2.5μm (PM2.5) and <10μm (PM10) with hospital admission for PTB in Hainan, a tropical province in China. We collected individual data on patients hospitalized with PTB, PM 2.5 , PM 10 , and meteorological data from 2016 to 2019 in Hainan Province, China. Conditional logistic regression models with a time-stratified case-crossover design were used to assess the short-term effects of PM2.5 and PM10 on hospital admission for PTB at a spatial resolution of 1 km × 1 km. Stratified analyses were performed according to age at admission, sex, marital status, administrative division, and season of admission. Each interquartile range (IQR) increases in the concentrations of PM 2.5 and PM 10 were associated with 1.155 (95% confidence interval [CI]:1.041-1.282) and 1.142 (95% CI:1.033-1.263) hospital admission risks for PTB at lag 0-8 days, respectively. The stratified analyses showed that the effects of PM2.5 and PM10 were statistically significant for patients aged ≥65 years, males, married, and those residing in prefecture-level cities. Regarding seasonal differences, the associations between PM and hospital admission for PTB were statistically significant in the warm season but not in the cold season. The effect of PM2.5 was consistently stronger than that of PM10 in most subgroups. Shortterm exposure to PM increases the risk of hospital admission for PTB. The potential impact of PM with smaller aerodynamic diameter is more detrimental.Our findings highlight the importance of reducing ambient PM level to alleviate the burden of PTB.